Research on Efficient Routing Algorithm Based on Dynamic Segmentation Network Coding - Li, Cong; Wu, Yonghao (2018 International Conference on Intelligent Transportation, Big Data & Smart City (ICITBS), 2018)
In order to solve the problem of existing routing algorithms, an efficient routing algorithm based on dynamic segmentation network coding (ERBNC) is proposed. By compressing the header of the encoded packet, deleting the redundant ACK packet and setting the priority of sending the encoded packet, the proposed algorithm reduces the network overhead and packet average end-to-end delay. The simulation experiments of ERBNC algorithm, dynamic segmented network coding (DSNC) algorithm and segmented network coding (SNC) algorithm were completed by using OPNET simulation software. The performance of various algorithms is compared and analyzed. The simulation results show that the ERBNC algorithm can effectively reduce the network overhead and reduce the average end-to-end delay of data packets.